“The Man Who Clashed with Khrushchev”: Ernst Neizvestny in the American Press in the 1960s–1980s - Riznychok, Irina A. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2023)
This article is devoted to the reception of Ernst Neizvestny’s art by the American daily and specialised press between the 1960s and 1980s. The research focuses on constructing the heroic image of Ernst Neizvestny based on several clichйs that are well-established in American culture: a fighter for freedom in art and an oppressed artist, “an artist in exile” after emigration. This article aims to fix the changes in the reception of Ernst Neizvestny’s oeuvre by American critics and journalists at different stages of the Cold War. The interdisciplinary approach contains the social, historical, and political factors that underlie artistic practice and necessitate the use of methods from different areas of the humanities including media and cultural studies. The main sources are reviews of solo exhibitions, interviews with the artist, notes, and articles in the American press. They are supplemented by video interviews with the sculptor from the archives of the National Centre for Contemporary Art (part of the Pushkin State Museum of Fine Arts) and the Garage Museum of Contemporary Art, Neizvestny’s published correspondence, as well as historical archival materials. If in the publications of the 1960s and 1970s, the authors were most interested in the relationship between Neizvestny and the Soviet authorities, at the end of the Détente, more analytical materials on art history appeared. The author concludes that the actualisation of a particular image depended on social and political factors, changes in the international cultural landscape, and the nature of the relationship between the two superpowers. The construction of the heroic image of Neizvestny in the US media became one of the tools of anti-Soviet propaganda in the cultural confrontation. An analysis of the reception of E. Neizvestny’s artworks helps reveal the ways in which ideas about Soviet art were produced and spread in American culture during the Cold War.